1971
DOI: 10.1111/j.1476-5381.1971.tb07192.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bronchodilator and cardiovascular actions of salbutamol, isoprenaline and orciprenaline in guinea‐pigs and dogs

Abstract: Summary1. Bronchodilator and cardiovascular actions of salbutamol and isoprenaline have been compared in guinea-pigs and dogs. Orciprenaline was also included in some experiments. 2. All three drugs antagonized acetylcholine-induced increases in pulmonary resistance. In addition they increased heart rate and decreased arterial blood pressure.3. Compared with isoprenaline, salbutamol has relatively stronger actions on bronchial and vascular /3-adrenoceptors than on cardiac 3-adrenoceptors, on which its action i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
28
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 25 publications
10
28
0
Order By: Relevance
“…This may have been because resting pulmonary resistance was low, as has also been observed in anaesthetized animals by other workers (Lulling, Prignot & Lievens, 1968). Since satisfactory dose-response curves to isoprenaline are obtained by measuring the inhibitory effect of the drug against acetylcholine-induced increases in pulmonary resistance (Daly, Farmer & Levy, 1971), this method was adopted for use in the present experiments.…”
Section: Preparation Of Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been because resting pulmonary resistance was low, as has also been observed in anaesthetized animals by other workers (Lulling, Prignot & Lievens, 1968). Since satisfactory dose-response curves to isoprenaline are obtained by measuring the inhibitory effect of the drug against acetylcholine-induced increases in pulmonary resistance (Daly, Farmer & Levy, 1971), this method was adopted for use in the present experiments.…”
Section: Preparation Of Animalsmentioning
confidence: 99%
“…Pulmonary resistance was measured as described by Daly et al (1971). A dose of acetylcholine, selected to give a submaximal increase of approximately 3-fold in pulmonary resistance, was administered intravenously at 5 min intervals until constant responses were obtained.…”
Section: Preparation Of Animalsmentioning
confidence: 99%
“…The attenuation of the vasodilator responses to intra-arterial noradrenaline and adrenaline by propranolol (Figure 1) and the consequent potentiation of the hepatic arterial vasoconstrictor responses to these catecholamines, particularly to adrenaline (Figure 3 adrenoceptor stimulant, salbutamol (Daly, Farmer & Levy, 1971) and the selective P,B-adrenoceptor antagonist atenolol (Hainsworth et al, 1974).…”
Section: Assessment Ofdrug Effectsmentioning
confidence: 99%
“…These experiments revealed the presence of P-adrenoceptors which were stimulated to cause hepatic arterial vasodilatation by isoprenaline and also by adrenaline and noradrenaline, but not by phenylephrine. Subsequently, the nature of the fl-adrenoceptors in this vascular bed was examined by using the selective /2-adrenoceptor stimulant salbutamol (Daly, Farmer & Levy, 1971) and the selective P,-adrenoceptor antagonist atenolol (ICI 66082) (Hainsworth, Karim & Stoker, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Because the technique is non-invasive, no measurements of blood pressure or heart rate were made; nonetheless, salbutamol was assumed to have been given in an effective dose (0.1 mg/kg) because it was much higher than has been reported to cause bronchodilation in dogs (Daly, Farmer & Levy, 1971). Kneussel & Richards (1977) showed that a-adrenoceptors were present in the tracheal and bronchial smooth muscle of tissue only from patients with chronic obstructive pulmonary disease, but normal human or canine airway muscle did not respond to noradrenaline, suggesting that there is usually an absence of a-adrenoceptors in this tissue.…”
Section: Discussionmentioning
confidence: 99%